The mythical speech as a tool for the Afro-descendant political claim in Changó, el gran putas of Manuel Zapata Olivella - del Campo Sotomayor, Josefina (2022)
The main objective of this article is to analyze the relevance of the mythical discourse in the novel Changó, el gran putas (1983) of the Colombian writer Manuel Zapata Olivella. It seeks to understand that this discourse is present in the work on three levels, which despite being different, constantly complement and intertwine: the first level of them is the mythical discourse as philosophy. For the understanding of this level, you will realize the Muntú worldview and Yoruba religion that is presented in the narrative. The second level is the myth as a narration, delving into the story of the curse of Chango that takes place in the novel. And, the third level is the myth as an engine of action, analyzing the relevance that certain characters have within the plot in relation to the material and political evolution of Afro-descendant peoples. All this to verify that the mythical discourse does not fulfill a merely narrative or contemplative function of an origin or a distant past, but rather constitutes a tool for cultural and political vindication for Afro-descendant peoples in America.